Preimaginal morphology of the genera Salpingogaster Schiner, 1868 and Eosalpingogaster Hull, 1949 (Diptera: Syrphidae), with its systematic implications - Pérez-Bañón, Celeste; Arcaya, Evelin; Mengual, Ximo; Rojo, Santos (Zootaxa, 2013)
The puparium of Salpingogaster nigra and Eosalpingogaster umbra are described, and diagnosis and illustrations are provided. The morphology of immature stages of the genera Salpingogaster and Eosalpingogaster are studied and compared for the first time. The results are in agreement with previous molecular analyses that recognise both genera as valid. We found two different puparium morphotypes for E. umbra and discuss the improbability of immature sexual dimorphism in this species. An identification key is also provided for all species with known puparia.